Water in medieval intellectual culture: case-studies from twelfth-century monasticism - Smith, James L. (Cursor mundi, 2017)
This study examines the significance and the deployment of fluid imagery in the composition, narration, and recollection of organised thought in the High Middle Ages through a blend of environmental and intellectual history. This volume provides a new contribution to the understanding of twelfth-century monasticism and medieval intellectual culture by exploring the relationship between water and the composition of thought. It provides a fresh insight into twelfth-century monastic philosophies by studying the use of water as an abstract entity in medieval thought to frame and discuss topics such as spirituality, the natural order, knowledge visualization, and metaphysics in various high medieval texts, including Godfrey of Saint-Victor's 'Fons Philosophiae', Peter of Celle's letter corpus, and the 'Description of Clairvaux'